METHODS OF TRAINING AND ASSESSMENT WITH AN UPDATED PROGRAM IN COMPUTER SCIENCE - A.R. А.Р.; Rakhymzhanova А.А.; Cherikbayeva А.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses in detail how to conduct elective lessons for high school students and final grades for students. In the course of the final assessment, we studied the development of cognitive abilities of students using the capabilities of computer technology, the formation of the ability to work independently, the provision of guidance, as well as the effectiveness of elective classes and methods used today. It was also noted that the final assessment can be carried out in various ways, including simple and convenient in electronic form, and that in order to improve the quality of training, it is necessary to first improve its methodology. The effectiveness of elective courses and the methods used to date have been studied. Given the rapidly growing global education available today, it was concluded that the use of new technologies to increase the effectiveness of schooling can be successfully used.